Expert panel opinions on carbon sequestration through bamboo utilisation in Malaysia: Rehabilitation of tin mines - Marcela Pimid; Kumara Thevan Krishnan (IOP Publishing, 2024)
Tin mining was once crucial to Malaysia's economy, but its decline left large areas of land severely degraded with poor soils and minimal vegetation. Bamboo has become a promising alternative for ecological restoration in these areas, but the understanding of carbon sequestration using bamboo remains limited. The study has two main objectives: (1) to evaluate the existing practices of carbon sequestration using bamboo in Malaysia, and (2) to assess the benefits of bamboo cultivation for its ecological functions and economic viability. This study investigates the perspectives of experts on the use of bamboo for carbon sequestration, particularly in the rehabilitation of tin mines in Malaysia, through panel expert interviews. The results showed that carbon sequestration in Malaysia is still in its early stages. Understanding of bamboo's capacity to absorb CO₂ and release oxygen varies among stakeholders. The experts recommended two bamboo-based benefit models: (1) using bamboo for carbon sequestration on degraded tin mining land, and (2) producing high-value downstream bamboo products such as bamboo biochar, bamboo panels, bamboo-based food, and handicrafts. The panel identified major challenges to bamboo utilisation in Malaysia, including land use competition, the need for specialised knowledge in bamboo cultivation, effective regulations, funding, and the willingness of the industry to engage with relevant stakeholders. Bamboo's key characteristics include rapid growth, high carbon absorption capacity, and its ability to stabilise soil. Recommendations for improving the use of bamboo in tin mine rehabilitation include enhanced training programs for local farmers, revisions to government incentives and policies, and further research into suitable bamboo species for rehabilitating tin mines or degraded land.